Notes on a new marine peritrichous ciliate (Ciliophora: Peritrichida), Zoothamnium xuianum n. sp., with redescription of Z. paraentzii Song, 1991 from northern China - Sun, Ping; Ji, Daode; Song, Weibo (Zootaxa, 2005)
The morphology, infraciliature and silverline system of two marine peritrichous ciliates, Zoothamnium xuianum n. sp. and Z. paraentzii Song, 1991, collected from a shrimp-hatching plant in northern China, were investigated using both in vivo and silver impregnation methods. The new species is recognized by the following characters: colony alternatively branched, zooids in vivo about 45 × 30 μm with single-layered peristomial lip; contractile vacuole apically located; macronucleus band-like and transversely positioned; more than 50 striations from peristomial area to aboral trochal band, about 14 from aboral trochal band to scopula; three equally long kineties in peniculus 3 parallel to each other. Based on both the Qingdao population and the original description, an improved diagnosis for Z. paraentzii is suggested: marine Zoothamnium with irregularly dichotomously branched stalk; zooid 50–80 × 25–45 μm in vivo with single-layered peristomial lip; contractile vacuole apically positioned; macronucleus C-shaped, transversely orientated; number of silverlines between anterior end and aboral trochal band about 75–83, between aboral trochal band and scopula, 28–33; inner row of peniculus 3 displaced from the other two and converges with peniculus 1 at aboral end.